A comparison of rock physics models for stress-related seismic azimuthal anisotropy. Issue 5 (3rd September 2019) - Bustamante Restrepo, Jefferson; Shragge, Jeffrey; Lumley, David
ABSTRACT: Improving the accuracy of seismic wave propagation for imaging and inversion purposes often requires evaluating the validity of any underlying anisotropic assumption. Over the previous decades different models have been proposed to address the assumption of azimuthally anisotropic media; however, to our knowledge there is no published comparative analysis between these models that would allow practitioners to understand which provides more accurate theoretical predictions given specific field conditions. We evaluate two rock physics models for azimuthal anisotropy in widespread use (Mavko and Sayers) to determine which offers the better predictive power for benchmark laboratory data sets measured on three different kinds of dry rocks: Massillon Sandstone, Barre Granite and Ottawa Sand. We find that the Mavko model generally provides more accurate predictions, with a maximum 7% error for the consolidated Massillon Sandstone and Barre Granite rocks. Neither model provides very accurate approximations for Ottawa Sand due to the fact that this unconsolidated rock violates the underlaying assumption that the total rock compliance is affected only by the rock's matrix and crack compliances. We conclude that even though Mavko's approach provides more accurate predictions, both models are sufficiently accurate for simulating wave propagation in consolidated rocks with azimuthal anisotropy (e.g. well consolidated and cemented sandstones, and granites).